Formulasi Mikroemulsi Minyak dalam Air (O/W) yang Stabil Menggunakan Kombinasi Tiga Surfaktan Non Ionik dengan Nilai Hlb Rendah, Tinggi dan Sedang - Sih Yuwanti; Sri Raharjo; Pudji Hastuti; Supriyadi Supriyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
The aim of this research was to determine the proportion of oil, surfactant and water which could produce a stable O/W microemulsion using combination of three nonionic surfactants with low, high and medium HLB values; and to determine the role of surfactant with a medium HLB value in O/W microemulsion formulation. The first group of microemulsions were prepared using combination of Tween 80, Span 80 and Span 40 (80 %:10 %:10 %) with dif- ferent proportions of VCO:surfactant (1:3, 1:3.5 dan 1:4). The second goups of microemulsion were prepared using combination of Tween 80, Span 80 and Span 40 (90 %:5 %:5 %) with different proportions of VCO:surfactant 1:4,1:4.5 dan 1:5. The stability of microemulsion was determined during storage at room temperature and after being ovened at 105 0C 5 hours and centrifuged at 2300 g 15 minutes. Microemulsion stability was determined by measur- ing absorbance of the microemulsion at 502 nm and then converted to turbidity (%). In order to determine the role of surfactant with a medium HLB value in the formulation of O/W microemulsion, one set microemulsions were made without surfactant with a medium HLB value, and another set of microemulsions were prepared with different ratios of low and medium HLB surfactant (1:1, 2:1 and 1:2). The most stable microemulsion was achieved when the proportion of VCO:surfactant:water was 4:20:76 and combination of Tween 80:Span 80:Span 40 with the ratio of 90:3.33:6.67. A more stable O/W microemulsion could be obtained when surfactant with a medium HLB value was added to O/W microemulsion formulation. Surfactant with a medium HLB value would link the oil phase and water phase with sur- factant layer, interaction of surfactant-oil and surfactant-water increased. It provided a smooth transition between oil phase and water phase, and the microemulsion became more stable.ABSTRAKTujuan dari penelitian ini adalah untuk menentukan proporsi minyak, surfaktan dan air yang dapat menghasilkan mik- roemulsi minyak dalam air yang stabil menggunakan kombinasi tiga surfaktan non ionik dengan nilai HLB rendah, tinggi dan sedang; dan mengetahui peran surfaktan dengan nilai HLB sedang dalam formulasi mikroemulsi minyak da- lam air. Kelompok mikroemulsi yang pertama disiapkan dengan kombinasi surfaktan Tween 80, Span 80 dan Span 40 (80 %:10 %:10 %) dan variasi proporsi VCO:surfaktan 1:3, 1:3,5 dan 1:4. Kelompok mikroemulsi yang kedua disiap- kan dengan kombinasi surfaktan Tween 80, Span 80 dan Span 40 (90 %:5 %:5 %) dan variasi proporsi VCO:surfaktan1:4, 1:4,5 dan 1:5. Uji stabilitas mikroemulsi dilakukan dengan disimpan pada suhu kamar, dioven 105 0C selama 5 jam dan disentrifuge 2300 g selama 15 menit. Pengamatan stabilitas mikroemulsi dilakukan dengan mengukur absorbansi mikroemulsi pada λ 502 nm yang dikonversi menjadi persen turbiditas. Untuk mengetahui peran surfaktan dengan HLB sedang maka dibuat mikroemulsi tanpa surfaktan HLB sedang, dan juga dibuat mikroemulsi dengan variasi rasio surfaktan HLB rendah dan sedang yaitu 1:1, 2:1 dan 1:2. Mikroemulsi paling stabil diperoleh dari formula dengan proporsi VCO:surfaktan:air = 4:20:76 dengan kombinasi surfaktan Tween 80:Span 80:Span 40 = 90:3,33:6,67. Pe- nambahan surfaktan HLB sedang pada formulasi mikroemulsi minyak dalam air lebih menstabilkan mikroemulsi yang dihasilkan. Surfaktan HLB sedang menjembatani fase minyak dan air dengan lapisan surfaktan sehingga meningkatkan interaksi surfaktan-air dan surfaktan-minyak, transisi antara fase minyak dan fase air menjadi lebih halus dan mikro- emulsi menjadi lebih stabil.